ANALISA PRIORITAS KENDALA PENGGUNAAN BAHAN FIBERGLASS BAGI NELAYAN PULAU BENGKALIS - Siswandi B (INOVTEK POLBENG, 2020)
For residents who live in coastal areas, most of them are engaged in traditional vessels which are generally made of wood. over time wood materials are increasingly difficult to obtain. Most of the Bengkalis people have known about fiberglass material as an alternative for construction of vessels, but the application of fiberglass material is only a small while other fishermen still use wood as their shipbuilding material. Based on these matters, it is necessary to evaluate and analyze related to the interests and constraints of Bengkalis fishermen on fiberglass material as a substitute for wood materials in shipbuilding. by distributing questionnaires to the fishing community and analyzing by using AHP (Analythic Hierarchy Process), the priority constraints that become problems for the fishing community of Bengkalis island are "cost of building fiberglass vessels" with a value 30% and the next problem is "availability of materials fiberglass "with a value 12%.